AWAL BULAN HIJRIYAH KITAB ITTIFAQ DZATIL BAIN - Sayful Mujab (YUDISIA : Jurnal Pemikiran Hukum dan Hukum Islam, 2013)
Scripture Ittifaq Dzatil Bain categorized into hisab hakiki bit tahkik bit, but in its calculations to determine the beginning of the new moon of Shawwal 1427 H height of more than 2 degrees until Romadlon only 29 days old. It is different from other books that also kind of book that Bain Dzatil Ittifaq occured that hilal height no more than 1 degree until months Romadlon can be istikmal to 30 days. Depart from this difference, the authors attempt to analyze how the accuracy of scripture used by Bain Dzatil Ittifaq in determining early Hijri month, especially early Shawwal 1427 AH From the analysis of the calculation results in a book that Dzatil Ittifaq Bain should be analyze again, although still can be used as a means of determining the beginning of Hijri.Keyword: New Month, Hilal, Ittifaq Dzatil Bain